Implementasi Nilai Pendidikan Karakter di SD Negeri 03 Tebat Karai Kabupaten Kepahiang - Ahmad Isna Muhdi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This research is about the implementation of character education values in SD Negeri 03 Tebat Karai, Kepahiang. This research has following objectives: (1). To find the implementation of character education value in SD Negeri 03 Tebat Karai. (2). To find the support factors and inhibit factors in the implementation of character education values at SD Negeri 03 Tebat Karai. This research was carried out directly at SD Negeri 03 Tebat Karai using descriptive qualitative methods, data collection techniques using interviews, observation and documentation. Data wettability technique uses triangulation techniques. Data validation techniques use data reduction methods, presenting data and drawing conclusions. The results of this study are (1) Implementation of character education values at SD Negeri 03 Tebat Karai is a program of implementing a character education curriculum, implementing character values in learning, implementing character values in school activities and implementing character values in daily activity in the school environment. (2) Supporting factors in the implementation of character education values at SD Negeri 03 Tebat Karai is teachers commitment, infrastructure, support from parents, and the environment. The inhibiting factors in the implementation of character education values at SD Negeri 03 Tebat Karai are less study hours of Islamic education, student motivation, the environment and misuse of technology.